Is palatal injection mandatory prior to extraction of permanent maxillary tooth: A preliminary study - G Raja Sekhar; T Nagaraju; KolliGiri; V Nandagopal; R Sudheer; Sravan (Wolters Kluwer Medknow Publications, 2011)
Introduction: Even after the invention of the modern injection techniques, palatal injection still remains a painful experience for patients, and this pain is attributed to the presence of rich nerve complement and displacement of palatal mucosa during anesthesia. Objective: The aim of the present study was to demonstrate if lidocaine HCl could provide palatal anesthesia if given buccally during maxillary tooth removal without the need for a palatal injection. Materials and Methods: The study group consisted of 75 patients, and 25 were controls. All the patients in the study group had unilateral extractions. In 75 patients, 2 ml of 2% lidocaine HCl with 1:80,000 epinephrine was injected into the buccal vestibule of tooth indicated for extraction without palatal injection. After 8 min, the extraction of maxillary tooth was carried out. Twenty-five subjects in the control group underwent same protocol with palatal injection. All the patients completed a faces pain scale (FPS) and a 100 mm visual analog scale (VAS) after extraction. Statistical Analysis Used: Unpaired t test and Chi-square test. Results: According to VAS and FPS scores, when comparison was carried out between permanent maxillary tooth removal with and without palatal injection, the difference in the pain levels were not statistically significant (P>0.05). Conclusion: The extraction of permanent maxillary tooth is possible by depositing 2 mL of lidocaine to the buccal vestibule of the tooth without the need for palatal anesthesia.